WUJUD DAN FUNGSI ALIH KODE PENUMPANG DAN AWAK BUS TRAYEK JEPARA-SEMARANG (KAJIAN SOSIOLINGUISTIK) - Wulansari, Nanik (Sastra Indonesia, Fakultas Ilmu Budaya, 2013)
This research aimed to describe the variation form of code switching, explaining the function of code switching and code switching determinants on speech passengers and crew-bus route Semarang-Jepara. This research is a qualitative descriptive study using a sociolinguistic approach. To achieve the objectives of this study, researchers refer to the theory of Hymes 1974 Suwito (1985) and Widjajakusumah 1981. Collecting data in this study through observation using advanced techniques. Refer involved a conversation (SLC), consider the conversation involved free (SBLC), records, and record. The results showed that the variation of code switching passengers and crew-bus route Semarang-Jepara is a the internal code switching. Over the internal code switching is a code switcing inter-language, that is from Indonesian to Javanese and from Javanese to Indonesian, and code switching between speech level, namely from language Java Ngoko to language Java Madya, language Java Madya to language Java Ngoko, language Java Ngoko to language Java Krama, language Java Krama to language Java Ngoko. Code switching function is found, which is to familiarize or stretch your communication, to offer and provide information, to provide security to passengers, to convey a sense of humor, and to save time. Determinants over the code is found, the setting and scene, participant, ends, key, genre: language diversity kolokial. Keywords: code switching, a form of code switching, code switching function, passengers, and crew bus.